PENGATURAN PENYELESAIAN PELANGGARAN OLEH MEDIA MASSA TERHADAP PEMBERITAAN IDENTITAS ANAK YANG BERHADAPAN DENGAN HUKUM - Rita Wati; Emilda Firdaus; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Press in performing journalistic has the indepedence and freedom in the search for, acquire, store, process and convey information to the public to pay attention to children’s rights, because the news of the identity of the child in both the media print and electronic media could have an impact not good for the growth and development of children physically, mentally or socially. The rule of law that gives sanction to the mass media or press a violation has been significantly reinforced in the law number 40 of 1999 on the press. The purpose of this research is to know how the actual settlement and sanction in case of violations committed by the media towards releasing the identity of the children in conflict with the law. The results on this study that settlemen can be trough Article 5 of the right to respond and Article 15 on the press council, as well as snction against the mass media is in violation of criminal sanctions fine of reprimands, a warning or moral sanction an apology publicly. The effort, which is expected that the media or press in this news should respect the rights and obligation to disseminate information or news accurately and balanced. In the sanction of law number 40 of 1999 on the press to clarify the position of the pers in the eyes of the law to the justice and legal certainty.Key words: Children - Press - Violations - Sanction